Myocardial viability with a new technique in the echocardiogram of stress. - Leonel de Armas Rodríguez; Carlos Yun Angarica; Niurka Moreno Rodríguez; Juan Prohías Martínez; Angel G. Obregón Santos (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Introduction: Inside the different diagnostic methods to identify myocardial viability, the stress Echocardiography is one of the broadly most utilized in the clinical practice. Objective: To determine the precision in the diagnosis of viable myocardium of digitized images of stress echocardiography with Dobutamina. Methods: To 15 patients in those that areas of myocardial viability were detected, through the images kept in the hard disk of a computer, and that they were accepted for treatment interventionist of angioplastìa more stent, they were carried out ventriculography later on, to contrast with the realized previous diagnosis. The Positive Predictive Value (VPP) was determined, the stocking of the Ejection fraction and the Index of myocardial contractility. Results: The viability for treatment interventionist was reached in the 15 patients proposed by echocardiography, and there was improvement of the ejection fraction, of the contractility index and the angina. The VPP was of 100%. Reoclusion was verified to the 30 days of the intervention in 13,3% of the patients. Summations: The digitized images allow a better real quantitative analysis outside of the ecocardiograph, with high precision and easy access.